2007
DOI: 10.1124/mol.107.038331
|View full text |Cite
|
Sign up to set email alerts
|

The Small Molecule NS11021 Is a Potent and Specific Activator of Ca2+-Activated Big-Conductance K+ Channels

Abstract: Large-conductance Ca 2ϩ -and voltage-activated K ϩ channels (Kca1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
112
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 112 publications
(119 citation statements)
references
References 21 publications
7
112
0
Order By: Relevance
“…To illustrate how efficacious the GoSlo-SR family of compounds were, we compared the effects of two well established BK channel openers, NS1619 [21] and NS11021 [12] on these currents. Figure 5A shows a typical example in which we applied NS1619 (orange line) at a concentration of 10 µM, to a patch containing approximately 23 BK channels.…”
Section: Structure Activity Relationship (Sar)mentioning
confidence: 99%
See 3 more Smart Citations
“…To illustrate how efficacious the GoSlo-SR family of compounds were, we compared the effects of two well established BK channel openers, NS1619 [21] and NS11021 [12] on these currents. Figure 5A shows a typical example in which we applied NS1619 (orange line) at a concentration of 10 µM, to a patch containing approximately 23 BK channels.…”
Section: Structure Activity Relationship (Sar)mentioning
confidence: 99%
“…[6] Consequently, the pharmaceutical industry has invested significantly in trying to target smooth muscle function by developing novel BK channel modulators to help treat disorders such as urinary incontinence. [6][7][8][9][10] Although a large number of chemically diverse BK channel openers have already been developed, [8,9] only a few studies [11][12][13] have focused on examining the effects of these compounds across a wide voltage range to include physiological potentials (~−100 mV to 0 mV). [10][11][12] Instead, the majority of studies have focused on the ability of compounds to open channels only at potentials some 50 to 100 mV more positive than a cell is ever likely to encounter in vivo.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…These results suggest that BK channel activators could represent a novel therapeutic approach for treating overactive bladder. However, despite the development of a large number of BK channel openers over the last two decades (23)(24)(25)(26)(27)(28)(29), they have failed to progress through clinical trials, because they showed poor efficacy, presumably due to their lack of effect at physiological membrane potentials, combined with a reduction in BK channels in patients with overactive bladder (30).…”
Section: +mentioning
confidence: 99%